Case Report of Calciphylaxis Secondary to Calcium and Vitamin D3 Supplementation. Issue 2 (March 2017) - Storan, Eoin R.; O'Gorman, Susan M.; Murphy, Annette; Laing, Mary
Background: Calciphylaxis is a rare disorder that is very unusual outside the setting of end-stage kidney disease. Case Summary: A 64-year-old woman with normal renal function presented with painful leg ulcers. She had previously received 300 000 IU of vitamin D3 followed by daily calcium and vitamin D3 supplementation. A skin biopsy was consistent with calciphylaxis, and she was treated with sodium thiosulphate infusions and wound debridement. Conclusion: Calcium and vitamin D3 supplements are widely prescribed. We report a case of calciphylaxis triggered by calcium and vitamin D3 supplementation in a patient with none of the typical risk factors. Our patient had an excellent response to treatment with sodium thiosulphate.